Tumour suppressor TET2 safeguards enhancers from aberrant DNA methylation and epigenetic reprogramming in ERα-positive breast cancer cells. Issue 10 (3rd October 2022) - Lyu, Ruitu; Zhu, Xuguo; Shen, Yinghui; Xiong, Lijun; Liu, Lu; Liu, Hang; Wu, Feizhen; Argueta, Christian; Tan, Li
ABSTRACT: Aberrant DNA methylation is an epigenetic hallmark of malignant tumours. The DNA methylation level is regulated by not only DNA methyltransferases (DNMTs) but also Ten-Eleven Translocation (TET) family proteins. However, the exact role of TET genes in breast cancer remains controversial. Here, we uncover that the ERα-positive breast cancer patients with high TET2 mRNA expression had better overall survival rates. Consistently, knockout of TET2 promotes the tumorigenesis of ERα-positive MCF7 breast cancer cells. Mechanistically, TET2 loss leads to aberrant DNA methylation (gain of 5mC) at a large proportion of enhancers, accompanied by significant reduction in H3K4me1 and H3K27ac enrichment. By analysing the epigenetically reprogrammed enhancers, we identify oestrogen responsive element ( ERE ) as one of the enriched motifs of transcriptional factors. Importantly, TET2 loss impairs 17beta-oestradiol (E2)-induced transcription of the epigenetically reprogrammed EREs -associated genes through attenuating the binding of ERα. Taken together, these findings shed light on our understanding of the epigenetic mechanisms underlying the enhancer reprogramming during breast cancer pathogenesis.